Quantification of HIV RNA and Human Herpesvirus DNA in Seminal Plasma - Milenka Vargas-Meneses; Marta Massanella; Caroline Ignacio; Sara Gianella (Bio-Protocol, 2015)
Multiple viruses can co-infect the genital tract, modifying the immunologic and virologic milieu and possibly playing a role in viral transmission and pathogenesis. The aim of our studies has been to understand the complex relationships between HIV-1 RNA, and multiple human herpesviruses known to frequently replicate in the genital tract of HIV-infected men (i.e. cytomegalovirus [CMV], Epstein Bar virus [EBV], herpes simplex virus [HSV] types 1 and 2, and human herpesviruses [HHV] 6, 7 and 8) (Gianella et al., 2013a; Gianella et al., 2013b; Gianella et al., 2013c; Gianella et al., 2014). This protocol was designed to collect and process male genital secretion (GS), and to isolate and further quantify HIV RNA and DNA of seven HHV from seminal plasma using quantitative real time PCR technology.